Keanekaragaman Belalang (Orthoptera: Acrididae) padaEkosistem Sawah di Desa Banyuasin Kecamatan Riau Silip Kabupaten bangka - Riko Irwanto; Tissya Milly Gusnia (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2021)
The paddy field ecosystem is a place for interactions between plants and animals, especially between rice plants and grasshoppers. Grasshoppers act as eaters of rice plants, of course, become a threat to agriculture so that they can reduce agricultural productivity. This study aims to determine the diversity of Orthoptera: Acrididae in the rice fields of Banyuasin Village, Riau Silip District, Bangka Regency and the habitat conditions of Orthoptera: Acrididae in the rice fields of Banyuasin Village, Riau Silip District, Bangka Regency. This research is a descriptive quantitative research using purposive sampling method using insect net and handsorting techniques. Measurement of environmental factors is carried out by taking data on soil temperature, soil moisture, and light intensity. The research data were analyzed using the Shannon diversity index and the evenness index. Based on observations, there were 6 types of Acrididae family found in the rice field ecosystem, namely 16 individuals of Valanga nigricornis, 12 of Xenocatantops humilis, 11 of Phlaeoba fumosa, 13 Traulia azureipennis, 9 Oxya hyla and 3 Trimerotropis pallidipenni. The analysis showed that the diversity index of grasshoppers was 1.70 which was classified as moderate criteria and the evenness index was 0.41 which was classified as moderate. The locust habitat that has been obtained has optimal soil temperatures ranging from 35oC-45oC, with 50% soil moisture. Keywords: Acrididae, diversity, Ecosystem, Orthoptera, Rice Fields ABSTRAK Ekosistem sawah merupakan tempat terjadinya interaksi antara tumbuhan dan hewan khususnya antara tumbuhan padi dan Belalang. Belalang bertindak sebagai pemakan tumbuhan padi tentunya menjadi ancaman bagi pertanian sehingga dapat menurunkan produktivitas pertanian. Penelitian ini bertujuan untuk mengetahui keanekaragaman Orthoptera:Acrididae di ekosistem sawah Desa Banyuasin Kecamatan Riau Silip Kabupaten Bangka dan kondisi habitat Orthoptera:Acrididae di ekosistem sawah Desa Banyuasin Kecamatan Riau Silip Kabupaten Bangka. Penelitian ini berupa deskriptif kuantitatif dengan menggunakan metode purposive sampling dengan menggunakan tehnik insect net dan handsorting. Pengukuran faktor lingkungan dilakukan dengan mengambil data suhu tanah, kelembaban tanah, dan intensitas cahaya. Data hasil penelitian dianalisis dengan menggunakan indeks keanekaragaman Shanon, dan indeks kemerataan. Berdasarkan hasil pengamatan, didapatkan sebanyak 6 jenis family Acrididae yang terdapat pada ekosistem sawah, yaitu Valanga nigricornis sebanyak 16 individu, Xenocatantops humilis berjumlah 12 individu, Phlaeoba fumosa berjumlah 11 individu, Traulia azureipennis 13 individu, Oxya hyla berjumlah 9 individu dan Trimerotropis pallidipennis berjumlah 3 individu. Hasil analisis menunjukkan bahwa indeks keanekaragaman belalang sebesar 1,70 tergolong kriteria sedang dan indeks kemerataan sebesar 0,41 tergolong sedang. Habitat belalang yang telah didapatkan ini memiliki suhu tanah yang optimal mulai dari 35oC-45oC, dengan kelembaban tanah 50%. Kata kunci: Acrididae, Ekosistem, keanekaragaman, Orthoptera, Sawah